Molecular Allergy Diagnostics : Innovation for a Better Patient Management - Kleine-Tebbe, Jörg; Jakob, Thilo (Springer International Publishing : Imprint: Springer, 2017)
This book, based on a recent German publication, offers an overview of basic data and recent developments in the groundbreaking field of molecular allergology. It comprehensively explores the origin and structure of single allergen molecules ("components") and their utility in improving the management of type I, IgE-mediated allergic reactions and disorders like allergic respiratory diseases, food allergies, and anaphylaxis. Highly specific testing, called component-resolved diagnostics, aims to identify and utilize single molecules. Over 200 single allergens from plant or animal sources have been applied to single or multiplex laboratory testing for the presence of allergen-specific IgE. This leap in assay sensitivity and specificity has led to three major advances in patient management: discrimination between primary allergic sensitization and complex cross-reactivity, recognition of IgE profiles for certain allergens and identification of patients most likely to benefit from allergen-specific immunotherapy. The book discusses in detail the benefits and limitations of this 21st century technology, and offers suggestions for the use of molecular allergology in routine clinical practice. It is a "must read" for physicians treating allergic patients as well as scientists interested in natural allergic molecules and their interactions with the human immune system.
Keywords: Medicine.; Allergy.; Dermatology.; General practice (Medicine).; Respiratory organs -- Diseases.; Otorhinolaryngology.; Pediatrics.; elektronické knihy; electronic books